Engineering Educators’ Approach on Development of Mentorship Strategy at HITAM-A Qualitative Study - Binani, Shradha; Reddy, Nayini Varshitha; Patel, Mihir; Singh, Thakur Aryan (Journal of Engineering Education Transformations, 2025)
Mentoring plays a crucial role in fostering the success of all student demographics within engineering education. Particularly in the early stages of their careers, young engineers can significantly benefit from the guidance and encouragement provided by faculty mentors. Ensuring that engineers are adequately prepared, both academically and professionally, to enter the industry underscores the importance of enhancing undergraduate engineering colleges’ perspectives on mentoring. This study delves into the perceptions of engineering educators at an autonomous institution in South India regarding mentorship programs in undergraduate education, employing a qualitative approach to assess their viewpoints. A questionnaire featuring open-ended questions was utilized to interview a total of 15 engineering educators. Analysis of the faculty responses yielded several prominent themes, including perceptions of mentoring in engineering education, essential components of successful mentoring, considerations of physical and mental well-being, skill enhancement, delineation of short and long-term objectives, fostering trust and openness in mentor-mentee relationships, and the formulation of effective mentoring strategies. The study also scrutinized variations in participant responses based on their educational backgrounds and prior involvement in mentoring initiatives. Aligned with the Zone of Proximal Development (ZPD) model, which posits that mentors play a crucial role in facilitating both personal and professional advancement, the research underscores the significance of mentors as valuable assets for mentees’ growth. Additionally, the article examines the advantages and limitations associated with experienced engineers and educators serving as mentors for young engineers in practice. The findings of this research are intended to serve as a guideline for engineering institutions seeking to establish successful and comprehensive mentoring programs that promote mentees’ holistic development and career progression.